Left Atrial size in Rheumatic Mitral Stenosis: An evaluation on the basis of age and heart rhythm - Limbu, Yuba Raj (Nepalese Heart Journal, 2000)
In Rheumatic Mitral Stenosis (MS) the left atrial size (LAD) increases with the increment of pressure gradient between the left atrium and left ventricle and the chance of left atrial mural thrombi increases with the increment of left atrial size1.2. Two-dimensional echocardiography is a well established technique to assess the left atrial size3, LAD is measured by M-mode echocardiography in the standard parasternal long axis view4 and enlarged LAD in rheumatic mitral stenosis is seen in echocardiography1.2.